Pengaruh Variasi Produk, Harga, dan Suasana Tempat Terhadapkepuasan Konsumen - Elia Maruli; Ferdinand Romelus Anigomang; Yustina Maro (Peneliti.net, 2022)
Consumer satisfaction is a person's feeling of pleasure or disappointment that arises after comparing the expected product performance or results to the expected performance or results. This study aims to determine the effect of product variations, prices and atmosphere of the place on customer satisfaction at Celyn Café, Alor Regency. The sample in this study amounted to 50 people. Data collection using questionnaire techniques, observation and documentation study. Data analysis uses instrument tests consisting of validity tests, reliability tests; classic assumption test consisting of normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test. While testing the hypothesis using multiple linear regression analysis, with the t test and F test. The results showed that partially the variable product variation has a significant effect on consumer satisfaction, indicated by a significance value of the t test of 0.039. Partially, price has a significant effect on consumer satisfaction, indicated by a significance value of the t-test of 0.041 and partially, the atmosphere of the place has a significant effect on consumer satisfaction, indicated by a significance value of the t-test of 0.037. Simultaneously the variables of product variation, price and atmosphere of the place have a significant effect on consumer satisfaction at Celyn cafe in Alor district, indicated by a significance value of the F test of 0.002 or 0.2%.